Digital Solutions for Supporting Active and Healthy Aging and Elderly Care - Anikó Panna (Magyar Gerontológia, 2025)
The presentation discusses how the challenges associated with population ageing, particularly in the context of elderly care and quality of life, can be addressed through the use of information and communication technologies (ICT) and innovative solutions.